1990
DOI: 10.1002/arch.940130103
|View full text |Cite
|
Sign up to set email alerts
|

How parasitoids deal with the immune system of their host: An overview

Abstract: Insects have evolved many mechanisms that reduce their potential for serving as hosts for entomophagous species. Some of these mechanisms involve escape, mimicry, and repellancy, which are effective defense mechanisms against both predators and parasitoids. But, insects have a second line of defense against parasitoids and parasites. These may include repellancy and a cuticular barrier to invasion but they include several internal defenses that are collectively referred to as immune mechanisms. The current und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
1
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(117 citation statements)
references
References 179 publications
(159 reference statements)
4
110
1
2
Order By: Relevance
“…Small clutches may also result from larval mortality. Although early-instar larvae may be successfully encapsulated by the cricket, we found little evidence of encapsulation, perhaps because tachinid larvae use the host-encapsulation response to build a breathing tube (Vinson 1990).…”
Section: Clutch Sizecontrasting
confidence: 56%
“…Small clutches may also result from larval mortality. Although early-instar larvae may be successfully encapsulated by the cricket, we found little evidence of encapsulation, perhaps because tachinid larvae use the host-encapsulation response to build a breathing tube (Vinson 1990).…”
Section: Clutch Sizecontrasting
confidence: 56%
“…Larvae stung became motionless within half an hour and gradually took on a brown colour, swelled and subsequently died. This has already been observed in several parasitoids that release venom or a series of secretions associated with oviposition in hosts (Vinson, 1998) causing permanent paralysis and their death (Vinson, 1990;Quicke, 1997). Roundish melanic stains also appeared in the ovipositor's insertion points on the larvae body, as described in other eulophid species (Viggiani, 1964;Celli and Raboni, 1993).…”
Section: Behavioral Observationsmentioning
confidence: 74%
“…Polydnaviruses (PDVs) are essential for the survival of some endoparasitoids in their lepidopteran host haemolymph and are implicated in attenuating host immune responses and altering host development (Beckage & Gelman, 2004;Lavine & Beckage, 1995;Lawrence & Lanzrein, 1993;Stettler et al, 1998;Stoltz & Vinson, 1979;Vinson, 1990;Webb, 1998). Because PDV genes play important regulatory roles in compromising host immunity and causing host developmental arrest, it has been suggested that these genes offer opportunities for enhancing the virulence of insect pathogens (Beckage & Gelman, 2004).…”
Section: Introductionmentioning
confidence: 99%